Determinan Stunting pada Anak di Indonesia: Sebuah Tinjauan Literatur Sistematis - Meily Amelia1; wulan nur asih (MEJORA Medical Journal Awatara, 2025)
Child stunting remains a major public health problem in Indonesia and has long-term implications for child growth and human capital development. This study aimed to identify and synthesize the determinants of stunting among children in Indonesia based on published scientific evidence. A systematic literature review was conducted by reviewing relevant scientific articles on stunting determinants in Indonesia. Article searches were primarily performed through Google Scholar using stunting-related keywords. Articles were selected based on topic relevance, study setting in Indonesia, and availability of full-text publications. A total of four eligible articles were included and analyzed using descriptive and thematic synthesis. The findings indicate that stunting in Indonesia is a multifactorial condition influenced by determinants at individual, household, and community levels. Individual-level factors include child age, biological conditions at birth, and infant feeding practices. Household-level determinants involve parental education, socioeconomic status, food security, and living conditions. Environmental factors, particularly water, sanitation, and hygiene (WASH), as well as regional disparities and the role of community-based health services such as posyandu, also contribute to stunting risk. In conclusion, reducing stunting in Indonesia requires an integrated multisectoral approach that addresses nutrition, environmental conditions, and strengthening community-based health services.